The practice of reporting adverse events in a teaching hospital - Andréia Guerra Siman; Simone Graziele Silva Cunha; Maria José Menezes Brito (SciELO, 2017)
Abstract OBJECTIVE Understanding the practice of reporting adverse events by health professionals. METHOD A qualitative case study carried out in a teaching hospital with participants of the Patient Safety Center and the nursing team. The collection took place from May to December 2015, and was conducted through interviews, observation and documentary research to treat the data using Content Analysis. RESULTS 31 professionals participated in the study. Three categories were elaborated: The practice of reporting adverse events; Barriers in the effective practice of notifications; The importance of reporting adverse events. CONCLUSION Notification was permeated by gaps in knowledge, fear of punishment and informal communication, generating underreporting. It is necessary to improve the interaction between leaders and professionals, with an emphasis on communication and educational practice.